2017
DOI: 10.1016/j.athoracsur.2016.12.044
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Drugs Carried in Lipid Nanoparticles in Coronary Disease of Rabbit Transplanted Heart

Abstract: LDE-PACLI promoted strong improvement of cardiac allograft vasculopathy, but the decrease in coronary stenosis by LDE-MTX and LDE-MTX/PACLI was not significant. All three treatments decreased macrophage infiltration in the graft. These results may encourage future clinical trials to test this new therapeutic approach to coronary allograft vasculopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Four hours after ischemic induction, animals were intravenously treated LDE-MTX or unconjugated LDE in the concentration of 1 mg/kg. This LDE-MTX dose afforded considerable anti-inflammatory and tissue protective effects in experimental models of arthritis (Mello et al, 2013) and myocardial infarction (Maranhao et al, 2017) in our previous studies.…”
Section: Lde-mtxc Treatmentmentioning
confidence: 50%
See 2 more Smart Citations
“…Four hours after ischemic induction, animals were intravenously treated LDE-MTX or unconjugated LDE in the concentration of 1 mg/kg. This LDE-MTX dose afforded considerable anti-inflammatory and tissue protective effects in experimental models of arthritis (Mello et al, 2013) and myocardial infarction (Maranhao et al, 2017) in our previous studies.…”
Section: Lde-mtxc Treatmentmentioning
confidence: 50%
“…We have investigated the anti-inflammatory and neuroprotective effects of LDE-MTX in an experimental model of cortical ischemia, as previous studies reported promising anti-inflammatory and tissue protective actions of LDE-MTX following experimental arthritis (Mello et al, 2013), myocardial infarction (Maranhao et al, 2017) and other diseases Barbieri et al, 2017;Fiorelli et al, 2017;Gomes et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies suggest that systemic delivery of nanoparticles and emulsions containing chemotherapeutics concentrated in a transplanted heart can prevent vasculopathy 25,26. Yet others advocate for the use of nanoparticles decorated with immunotherapeutics as a delivery device for tissues such as allo-islets to allow for implantation under the shield of immunomodulating therapeutics 27.…”
Section: Discussionmentioning
confidence: 99%
“…Along with pre-treatment strategies, delivery mechanisms intended to allow for organ level immunosuppression while leaving the patient's global immune system intact may represent the future of organ specific immunosuppression. These disruptive technologies include micro and nanoparticles carrying immunosuppressants and chemotherapeutics, for example, delivered both systemically and directly to an organ allograft 25,26,28…”
Section: Discussionmentioning
confidence: 99%